Microfoundations for New Market Creation: Differences between Expert Entrepreneurs and Expert Managers - Dew, Nicholas; Read, Stuart; Sarasvathy, Saras D.; Wiltbank, Robert (Senate Hall, 2018)
Within the growing literature on new market development, much work focuses on the industry, competition and firm units of analysis. In this paper we complement these understandings of how new markets unfold with research examining how individual decision-makers think about the task of building new markets. We replicate an entrepreneurship protocol analysis study so we can contrast entrepreneurs' results with a novel sample of experienced corporate executives. We find these groups (a) employ significantly different heuristics that (b) generate different prospective outcomes; (c) the different heuristics aggregate into substantively different processes and (d) the heuristics and processes offer clear implications for theory in entrepreneurship, strategy and innovation management. Our work contributes to the literature by providing prescriptions for new market creation processes based on the cognitive microfoundations revealed in our study. Keywords: creation, new market, cognition, executive, entrepreneur, decision-making, protocol analysis
Keywords: creation|new market|cognition|executive|entrepreneur|decision-making|protocol analysis|expert